The Management of Short Circuits' Mechanism of CO2 Shielded Welding; IOP Conference Series: Materials Science and Engineering; Vol. 253 : International Scientific-Practical Conference: Innovations in Fuel and Energy Complex and Mechanical Engineering (FEC-2017) - Knyazkov A. F. Anatoly Fedorovich (2017, 2017)
Title screen